Between Control and More-than-Human Events: The Listening Experience in the Light of Speculative Pragmatism - Souza Lima, Henrique; Branco Germano, Gustavo; Campesato, Lílian; Nogueira Esteves, Lucia; Mapurunga, Marina; Bonafé, Valéria; Reis, Vicente (AM Journal of Art and Media Studies, 2021)
This paper presents an investigation into the relationship between listening and power in the context of information warfare through the theoretical framework of speculative pragmatism. The main objective is to investigate the possibility of thinking of the listening activity as a particular act of thought through the concepts of lived abstraction and subjectless individuation. For doing this, the first part of the article describes the relationship of reciprocal presupposition between current online information warfare and the production of a subjectivity tied to a narcissistic regime of subjection. The second part of this article describes the concept of lived abstraction, such as elaborated by philosopher Brian Massumi. The third part of this article consists of investigating the epistemological core of speculative pragmatism through Deleuze and Guattari’s concept of subjectless individuation, particularly the individuation of an event. In the last part, we speculate a possible understanding of listening as an act of thought that is potentially articulated outside the noological register of narcissism through the appreciation of a mode of artistic operation that work in a way of designing listening experiences. Article received: April 18, 2020; Article accepted: July 1, 2020; Published online: April 15, 2021; Original scholarly paper